Gastrointestinal risk factors and prescribing pattern of antiulcer agents in patients taking low-dose aspirin in Japan. (21st November 2017) - Iwasawa, Makiko; Wada, Kyoichi; Takada, Mitsutaka
Abstract: Objectives: To identify prescribing patterns of antiulcer agents in patients on low-dose aspirin (LDA) and to evaluate the number of gastrointestinal (GI) risk factors of the patients. Methods: A retrospective chart review of patients taking LDA was conducted at the National Cerebral and Cardiovascular Center in Japan. The rate of concomitant use of antiulcer agents and the risk of each patient to develop GI complications were evaluated. Results: Of the 314 patients, 64 were not on antiulcer agents and 55 of them had >1 risk factor. More patients not on antiulcer agents had started LDA before hospitalization. Conclusion: The rate of coprescribing antiulcer agents with LDA was high. However, the timing of initiating LDA therapy affected the prescribing pattern of antiulcer agents.